Pharmacologic Prophylaxis for Venous Thromboembolism Among Patients With Total Joint Replacement: An Electronic Medical Records Study. (March 2016) - Rosenman, Marc; Liu, Xianchen; Phatak, Hemant; Qi, Rong; Teal, Evgenia; Nisi, Daniel; Liu, Larry Z.; Parr, J. Andrew
Abstract : Patients who have total hip (THR) or knee (TKR) replacement have an elevated risk of venous thromboembolism (VTE). The American College of Chest Physicians guidelines recommend prophylactic anticoagulation. The aim of the study was to examine pharmacologic prophylaxis against VTE among patients with THR or TKR and to assess demographic and clinical correlates related to VTE prophylaxis. Using 15 years of data (1995–2009) from an electronic medical record system for an inner-city public hospital in the United States, we examined pharmacologic prophylaxis against VTE and associated factors in patients after THR (n = 242) and TKR (n = 317). Before the early 2000s, aspirin was the most common prophylaxis agent (THR, 61% and TKR, 65%), and 26% of patients with THR and 19% of patients with TKR did not receive prophylaxis. Enoxaparin use has increased since 2000, and warfarin is now the most common prophylaxis agent (THR, 70% and TKR, 61%). After controlling for time period, factors associated with prophylaxis pattern included obesity, hip fracture, and the surgeon's number of years in practice. VTE prophylaxis medications in patients with total joint replacement have changed over 15 years, in trends generally consistent with the evolution of guidelines. Obesity, history of hip fracture, and physician's experience are associated with the prescription of VTE prophylaxis medications.